Regulatory policy on ensuring sustainability of tax revenues of EU-28 countries - Abramova, A. S.; Chub, A.; Kotelevets, D.; Lozychenko, O.; Zaichenko, K.; Kupchyshyna, O. (Laplage em Revista, 2021)
The purpose of the article is to develop theoretical and applied principles for studying the stability and sustainability of tax revenues of the EU-28 and the introduction on this basis of a system of regulatory tax policy measures. The analysis of the stability of tax revenues of the studied countries is carried out due to a comprehensive approach, the methodology of which is based on a combination of static characteristics that demonstrate their state at a given time and GDP elasticity coefficients that determine the intensity of their dynamics. The scientific approach to the interpretation of the concept of "sustainability of tax revenues" is systematized. The state of stability and stability of tax payments in the EU-28 countries is analyzed, the main trends are identified. Led by classical principles and traditional measures of influence on tax policy, in particular, on the growth of tax revenues, an up-to-date view is proposed on the directions of implementation of regulatory tax policy in the studied countries.
Keywords: regulatory policy, tax policy, sustainability of tax revenues, tax burden, GDP, econometric modeling